High expression of N-type calcium channel indicates a favorable prognosis in gliomas. Issue 26 (30th June 2022) - Li, Guibin; Roy, Bhaskar; Huang, Xiaoqiang; Mu, Yafei; Yuan, Jiecheng; Xia, Yang; Song, Yue; Peng, Ziyue
Abstract : For the diagnosis and prognosis of glioma, the development of prognostic biomarkers is critical. The N-type calcium channel, whose predominant subunit is encoded by calcium voltage-gated channel subunit alpha1 B ( CACNA1B ), is mostly found in the nervous system and is closely associated with neurosensory functions. However, the link between the expression of CACNA1B and glioma remains unknown. We used ONCOMINE to explore the differences in CACNA1B expression among different cancers. We then conducted survival analysis and COX analysis using TCGA_LGG and TCGA_GBM datasets, which were divided into CACNA1B high and CACNA1B low based on the median. We examined the differences in other favorable prognostic markers or clinical characteristics between CACNA1B high and CACNA1B low using t tests. Differentially expressed genes were identified, and KEGG pathway enrichment was performed. We compared the expression of methyltransferases and analyzed the differentially methylated regions. Immunohistochemistry results were retrieved from the Human Protein Atlas database for validation purposes. CACNA1B was expressed at lower levels in gliomas, and, for the first time, we found that high expression of CACNA1B in gliomas predicts a good prognosis. Other favorable prognostic markers, such as isocitrate dehydrogenase mutation, 1p/19q codeletion, and O6-methylguanine-DNA methyltransferase promoter methylation, were increased in tandem with high expression of CACNA1B . Differentially expressed genes were enriched in multiple pathways related to cancer progression and aberrant epigenetic alterations were significantly associated with CACNA1B . High expression of N-type calcium channels indicates a favorable prognosis for gliomas. This study provides a better understanding of the link between gliomas and N-type calcium channels and may offer guidance for the future treatment of gliomas.